POLA CEKUNGAN DAN STRUKTUR BAWAH PERMUKAAN DITINJAU DARI HASIL ANALISIS GAYA BERAT DAN MAGNET DI DAERAH BANJARNEGARA, JAWA TENGAH BAGIAN SELATAN - Simon Hutubessy (Jurnal Geologi dan Sumberdaya Mineral, 2008)
Density of rocks of 2.85 gr/cm3   and magnet susceptibility of K=0.00023 e.m.u are interpreted as pre-tertiary basement, assumed to be transformed granite rocks. This basement underlies densities of rocks and magnet susceptibilities as follows: 2.74 gr/cm3  and K=0.000036 e.m.u, 2.66 gr/cm3   and 0.0 e.m.u, 2.43 gr/cm3   and K=0.03230 e.m.u, and 2.42 gr/cm3 and K=0.01458 e.m.u, interpreted as Tertiary sediment rocks around 1.5 to 6 km in thick, and Quarter sediment rocks such as: Jempangan volcanic rocks (Qjo), members of Ligung Formation Clay (Qtlc), members of Ligung Formation braccia (QTlb), terrace deposit (Qt), and alluvium (Qa). These basement and sediment rocks are intruded by density of rocks and magnet susceptibility; 2.84 gr/cm3   and K=0.00033 e.m.u, interpreted as igneous diorite rocks, as seen at C-D section and many are revealed in the researched area.Basins in the researched area are generally in direction of southwest-northeast, southeast-northwest, and also west- east due to a normal fault occurring in the researched area.The structure of strike slip  fault occurring in this area is generally in the directions of nearly north-south, southeast- northwest, and esat-west. Thrust faults in this area exist to the northwest of Banjarnegara, of southeast-northwest direction, with movement direction to the south. Thrust faults also exist to the south of the fault direction generally west- eats, and have movement direction to the north.Keywords: basement, Serayu valley, basin pattern, underground structure, Banjarnegara